Synthesis and Electrochemical Characterization of a Glass-Ceramic Li7P2S8I Solid Electrolyte for All-Solid-State Li-Ion Batteries. Issue 5 (3rd April 2018) - Choi, Seon-Joo; Lee, Sang-Hun; Ha, Yoon-Cheol; Yu, Ji-Hyun; Doh, Chil-Hoon; Lee, Youjin; Park, Jun-Woo; Lee, Sang-Min; Shin, Heon-Cheol
Abstract : Development of a tangible solid state battery has received great attention but there are various engineering challenges to overcome, especially for the scalable processing and the use of Li metal anode. In order to tackle these issues, we first evaluated the electrochemical stability of thio-LISICON solid electrolytes, i.e., Li10 GeP2 S12 (LGPS), Li7 P3 S11 (LPS), and Li7 P2 S8 I (LPSI), where the glass-ceramic LPSI electrolyte showed a superior compatibility with Li metal. Moreover, a superionic conductivity of 1.35 × 10 −3 S/cm could be achieved by optimizing the wet mechanical milling and the low-temperature annealing processes. Using this superior LPSI solid electrolyte, we evaluated the electrochemical performance of pellet-type and slurry-type all-solid-state cells with LiNbO3 -coated LiNi0.6 Co0.2 Mn0.2 O2 (LNO-NCM622)/LPSI composite cathode and Li metal anode. The initial discharge capacity of ∼150 mAh/g was achieved for the pellet-type test cell and ∼120 mAh/g for the slurry-type cell. Comparing the interfacial resistances of the two types of cells, strategies to enhance the performance and realize a scale-up fabrication of all-solid state Li-ion batteries are discussed.